Nutritional status, haematological and immunological changes and heavy metal exposure in victims post massive flood in Tumpat, Kelantan - Fauzi, Norshila (2018)
Massive flood known as “Bah Kuning” that hit Kelantan in December 2014 was the worst in the history of the state affecting health and socioeconomic status of the victims. There were immediate and delayed effects of the flood from the haematological and immunological aspects. There are limited studies pertaining to the physiological changes post disaster. This study aimed to assess the sociodemographic factors, nutritional status, heavy metal exposure, haematological & immunological parameters of the victims reflecting the impact of the 2014 massive flood. A crosssectional study among flood victims was conducted in Tumpat district of Kelantan from May until August 2015 involving 297 participants. The study was done 4 months post-event. Participants were recruited from house visits to answer questionnaires regarding sociodemographic and food security related questions. Blood samples were taken from two adults (female and male) in a household. The blood samples were then tested for full blood count (FBC), ferritin, lymphocyte subset analysis, serum immunoglobulin levels (IgG, IgA and IgM), red blood cell folate (RBC folate) and heavy metals analyses (cadmium, arsenic, plumbum and mercury). As a part of this study, a cross-sectional comparative study was done to compare the laboratory profiles among the flood and non-flood victims. The finding from the food security assessment showed that 71.6% were classified as food insecure category. Socioeconomic parameters were significantly associated with household food security, p=0.001. Eight participants were found anaemic and all participants had normal RBC folate while 27had high serum ferritin. There was no direct association between food security and laboratory parameters. In comparison with control participants (non-flood victims), haemoglobin was significantly lower (p=0.02) and total white blood cell (TWBC) was significantly higher (p=0.012) in male flood victims. Monocytes counts were found higher in both male and female victims, p=0.003 and p=0.048 respectively. The percentages and absolute counts of CD4 were higher while the percentages of CD8 showed significantly lower in male flood victims, p<0.05. Besides that, CD4:CD8 ratio was also significantly different in males, p=0.012 while serum immunoglobulins were all significantly higher in female flood victims, p<0.05. Heavy metals were detected in participants’ blood samples and in one well water sample but below the harmful cut off levels. In conclusion, the flood might have contributed to some subclinical health risk especially from the immunological changes seen among the victims. Although the findings could not be confirmed directly related to the flood effect, the result could be used to predict possible health complications that could occur if the socioeconomic problems and food-water securities were not handled appropriately post-event.